Ultimate pH values and bacteriological condition of meat and stress metabolites in blood of transported reindeer bulls - Wiklund, E.; Rehbinder, C.; Malmfors, G.; Hansson, I.; Danielsson-Tham, M-L. (Rangifer, 2001)
Twenty-three reindeer bulls, aged 2-3 years, fed during two winter months at the Vuolda reindeer research station in Arjeplog, Sweden, were used in the study. The first group of eight reindeer was moved from their feeding corral to a selection corral, captured by lasso and stunned with a captive bolt outside the selection corral. The second group of seven reindeer was moved to the selection corral, captured by lasso and restrained, after which they were loaded onto a lorry- and transported for 1 hour and then slaughtered. The third group of eight reindeer was moved to the selection corral and herded directly onto the lorry, without any manual handling. They were transported for 5 h and then slaughtered. In both transport groups, four reindeer were fitted with pre-programmed automatic blood sampling equipment (ABSE). ABSE sampled blood at predetermined times via a jugular vein catheter. Ultimate pH-values in three muscles (Mm. longissimus, triceps brachii and biceps femoris) were significantly lower in the group carefully handled and transported for 5 h compared with the other two groups. The physiological mechanisms behind these results are discussed. Samples from M. semimembranosus were collected at slaughter and after 2, 6 and 10 days of refrigerated storage (+4 °C). The samples were analysed for total counts of aerobic bacteria (pour-plated in Tryptone Glucose Extract Agar, Difco, incubated at 20 °C and 30 °C, respectively for 72 h), coliform bacteria 37 °C (pour-plated in Violet Red Bile Agar, Oxoid, incubated at 37 °C for 24 h), Enterococci (surface-plated onto Slantez and Bartley Agar, Oxoid, incubated at 44 °C for 48 h) and Bacillus cereus (surface-plated onto Blood Agar Plates (Blood Agar Base, Difco, supplemented with 5% defibrinated horse blood) 30 °C for 24 h). All samples fell in the range 'fit for consumption'. At slaughter, there was no difference in ASAT activity, urea and Cortisol concentrations between the two transported groups. However, the plasma ASAT activity and urea concentrations at slaughter were significantly lower in the non-transported group. In both transport groups, the plasma Cortisol concentrations increased during loading onto and unloading from the lorry. Abomasal lesions were observed in all treatment groups. It was concluded that reindeer showed an acute stress response to manual handling and transport.